ANALYSIS OF NEWS PORTAL DISCUSSION 'WAYANG ORANG PENGET' DELIGHTS MALANG THEATERGOERS ON JAKARTA POST - Simanjuntak, Anni Alvionita (JAMI: Jurnal Ahli Muda Indonesia, 2022)
Objective Critical discourse analysis is always interesting to study more deeply. The power of the media and public perceptions that make critical discourse research continue to grow. This helps readers understand the use of language because language is not just a means of communication, but is also used as an instrument to do something. Materials and Methods. The formulation of the problem of this research is how the critical discourse analysis of the van Dijk model is in the Jakarta Post 'Wayang Orang Penget' Delights Malang Theatergoers. This type of research is qualitative research because the data studied is news that has been transcribed. Data collection techniques in this study use observation and documentation techniques. Result. The results of the study show that in the reporting of "Wayang Orang Penyet", the Macro Structure reveals a larger size in writing the title and the quotation marks in writing 'Wayang Orang' to emphasize the discussion on the news portal. In Superstructer, Lead describes the situation on the Wayang Orang theater stage during the event, as well as describing the enthusiasm of the people in enjoying the performance. The lead then develops and takes the audience to the show. The microstructure is separated into Semantics, Syntax, Stylistics, and Rhetoric. Conclusion. This research notices the aspects such as Micro Structure, Super Structure, and Macro Structure. This news in the Jakarta Post port informs Wayang Orang Penget art performance held in Malang gets much attention from the audiences.